(3GdJMdjd GdGMUGFj ddHjGfGJ HGSJNOGe HQeLjI (B(SPSS VERSION (15-16 /s - (3CHhRjO, eMO NjQ Sdjes ((3YeGf(B: s (3OGQ LQjQ(B, s, 2009)
(3ebOeI aj GdJMdjd GdGMUGFj , echfGJ TGTI HQeLjI (Bspss (3GdJYGed eY eda GdHjGfGJ h JMQjQgG , bGFeI(Bdata (3h(Btransform(3, JeKjd GdHjGfGJ HjGfjG , GdGMUGA GdhUaj ,ENJHGQ GdaQVjGJ h GNJHGQ GdYjfI GdGMGOjI , GNJHGQ ebGQfI Hjf eJhSWj eLJeYjf , GNJHGQ cGj SchjQ , JMdjd GdJHGjf GdGMGOj h GdKfGFj h GdJHGjf GdeTJQc , GdGQJHGW h GdGfMOGQ GdHSjW h GdeJYOO , MGdI YedjI HGdJWQb Gdi hUa NUGFU YjfI GdOQGSI ,hUa abQGJ GdOQGSI , JYQja eJZjQGJ GdOQGSI h GNJHGQ GdaQVjGJ (B.s
(3eQGLY U(B.435s
Keywords: (3GdEMUGA GdBdjs; (3GdGMUGA GdhUajs; (3GdHQeLjGJs; (3GdJMdjd GdGMUGFjs; (3GdMGShHs